Untargeted lipidomics analysis in women with intrahepatic cholestasis of pregnancy: a cross‐sectional study. (7th December 2021) - Sun, X; Qu, T; Wang, W; Li, C; Yang, X; He, X; Wang, Y; Xing, G; Xu, X; Yang, L; Zhang, H
Abstract : Objective: To compare the plasma lipid profiles in women with normal pregnancies and those with mild or severe intrahepatic cholestasis of pregnancy (ICP). Our goal was to reveal lipidome‐wide alterations in ICP and delve into the pathogenesis of ICP from a lipid metabolism perspective. Design: Cross‐sectional study, including women with normal pregnancies, women with mild ICP and women with severe ICP. Setting: Gansu Provincial Hospital. Population: Women with ICP were recruited from October 2019 to March 2020 in Gansu, China. Methods: Untargeted lipidomics was used to analyse differentially expressed plasma lipids in controls, in women with mild ICP and in women with severe ICP ( n = 30 per group). For lipidomics, liquid chromatography and Q‐Exactive Plus Orbitrap mass spectrometry were performed. Main outcome measures: Differentially expressed lipids. Results: Thirty‐three lipids were differentially expressed in the severe and mild ICP groups, compared with the control group, and 20 of those were sphingolipids (ceramide, six species; sphingomyelin, 14 species). All differentially expressed sphingolipids in women with mild ICP were also differentially expressed in women with severe ICP; the fold change and significance of the differential expression were positively correlated with disease severity. Conclusions: We systematically characterized the lipidome‐wide alterations in mild and severe ICP groups. The results indicated a link between ICP and disordered sphingolipid homeostasis. Tweetable abstract: Abnormal sphingolipid metabolism is involved in the pathogenesis of ICP. Tweetable abstract: Abnormal sphingolipid metabolism involved in the pathogenesis of intrahepatic cholestasis of pregnancy. Linked article This article is commented on by L Gill & S Contag, pp. 889–890 in this issue. To view this minicommentary visit https://doi.org/10.1111/1471-0528.17060 .